‘The Daily Madness’ between Realism and Idealism – Parenthood and Academic Work (KULT_online, 2020)
After having become parents, (post-)graduate and doctoral students, as well as researchers further advanced in their careers, have to come to terms with the pivotal conflict revolving around time as an important resource. In order to help those parents prevent stress overload, Annette C. Cremer suggests a realistic outlook on parenthood in academia. In her handbook she offers detailed advice for students on how to organize life and work, as well as pointing out structural obstacles that need to be addressed and overcome.